Background colour and its impact on food perception and behaviour - Spence, C (Elsevier, 2018)
Colour affects many aspects of our lives. One area of particular interest in recent years has been the role of colour cues in the perception of food and drink. While the majority of this research has tended to focus on the impact of changing the colour of the product itself, there is now a growing body of scientifically-credible research (building on earlier anecdotal claims) that the colour of the background against which food and drink is served affects both people’s perception of it, and also their serving and consumption behaviour as well. In this review, the empirical evidence on this topic is summarized and the various mechanisms that have been put forward to account for such results outlined. Gaining a better understanding of when, and why, background colour impacts our food preferences, perception, and ultimately our behaviour, is likely to be important to chefs, food bloggers, restaurateurs, packaging designers, and those working on encouraging various special needs populations to consume more (or less).